Understanding kinetics and effect of process conditions during pretreatment of pine-sawdust (PSD) using torrefaction and solvolysis - Ikegwu, Ugochukwu Michael (My University, 2021)
The exploration and depletion of fossil fuels accompanied by the global warming and climate change challenge the world faces motivate the need for optimized pretreatment technique and efficient thermochemical conversion of biomass waste into energy at bench scale and industrial scale. This study focused on optimally using pine sawdust as a solid fuel. Particularly, this study aimed to understand the effect of process conditions on pine sawdust pretreatment (PSD). Two pretreatment techniques were considered: torrefaction process and solvolysis process. The process conditions studied between the two pretreatment techniques were based on literature and were benchmarked for easy comparison. Effects of process conditions on the pretreatment of PSD via the two techniques mentioned above and the kinetic analysis of the isothermal degradation of PSD during torrefaction were investigated. Research efforts on using biomass as an alternative fuel source have continued to gain more focus with emphases on pretreatment, which could result in efficient thermochemical conversion processes. This is because of the significant improvement in the fuel properties of biomass (such as energy densification, increase in carbon content, and deoxygenation) offered by pretreatment processes. Therefore, understanding the process conditions during biomass pretreatment is essential in producing high-quality fuel for energy production and designing an efficient energy generation plant. The effect of process conditions such as temperature, time, Nitrogen-to-Solid ratio (NSR) and Liquid-to-Solid ratio (LSR) on the pretreatment of waste pine sawdust (PSD) via torrefaction and solvolysis was studied. Desirability function approach and genetic algorithm (GA) were employed in the investigation. Response surface methodology (RSM) based on Box-Behnken Design (BBD) was used to investigate the effect of the process conditions mentioned above on the higher heating value (HHV), mass yield (MY) and energy enhancement factor (EEF) of biochar/hydrochar obtained from the waste PSD. A total of 17 experiments were designed each for torrefaction and solvolysis process. The benchmarked process conditions were temperature (200 –300 °C), time (30 –120 min) and NSR/LSR (4 –5). In this study, the operating temperature was the most influential variable influencing the pre-treated PSD's fuel properties, with NSR and LSR having the least effect. The oxygen-to-carbon ratio and the HHV of the pre-treated fuel sample were compared for the two investigated pretreatment methods. Solvolysis showed a higher reduction in the oxygen-to-carbon ratio (47 %)of the PSD, while 44 % reduction was obtained for the torrefaction process. A higher mass loss and energy content was also recorded for solvolysis than that of the torrefaction process. From the optimization process results, the accuracy of the optimal process conditions was higher for GA (299 °C, 30.07 min & 4.12 NSR for torrefaction and 295.10 °C, 50.85 min & 4.55 LSR for solvolysis) than that of desirability function based on RSM. Each predictive model's significance was established using Fisher's test, Probability value, coefficient of determination (R2) and Lack of Fitness test. The predictive model for the higher heating value during torrefaction recorded a predicted R2 of 0.9805 while solvolysis recorded a predicted R2 of 0.8593. The predictive model for the mass yield during torrefaction recorded a predicted R2 of 0.8942 while solvolysis recorded a predicted R2 of 0.9434.The developed models were reliable for evaluating the effect of the process conditions considered in this study by explaining at least 86 % (as seen in the predicted R2) of the variation in the fuel (PSD) physicochemical properties during torrefaction and solvolysis. The reaction kinetics of solid fuel is a critical aspect of energy production. This importance is because the fuel's energy component is determined during the process, and the overall fuel quality is evaluated to account for a defined energy need. In this study, a two-step first-order reaction mechanism was used to model the rate of mass loss of pine sawdust (PSD) during torrefaction using a thermogravimetric analyzer. The kinetic analysis was carried in a MATLAB environment using MATLAB R2020b software. Five temperature regimes including; 220 °C, 240 °C, 260 °C, 280 °C and 300 °C and retention time of 2 hours were used to study the mechanism of the solid fuel reaction. Similarly, a combined demarcation time (i.e. estimating the time that demarcates the first stage and the second stage) and iteration techniques were used to determine the actual kinetic parameters that described the fuel's mass loss during torrefaction process. The fuel's kinetic parameters were estimated, while the kinetic model developed for the process was validated using the experimental data. The solid and gas distribution of the pseudo-components in the reaction mechanism were also reported. The first stage of the degradation process was characterized by the rapid mass loss evident at the start of the torrefaction process. In contrast, the second stage was characterized by a slower mass loss phase which followed the first stage. The activation energies for the first and second stage were 10.29kJmol-1and 141.28 kJmol-1respectively, to form the solids. The developed model showed 98 –99.9 % accuracy in predicting the mass loss of PSD during torrefaction at various temperatures. The biochar produced from the torrefaction process contained a high amount of the intermediate product (Pseudo-component B) that may benefit energy production. However, the final amount of biochar formed at the end of the process increased with increase in torrefaction severity (i.e. increase in temperature and time). The outcome of this study has made available the technical set of data which can pave the way for further research in this field and offer relevant information for the implementation of these processes on a pilot scale. The knowledge derived from this study may also be extended to the pretreatment of other abundant and invasive biomass for efficient energy production
A thesis submitted to the School of Chemical and Metallurgical Engineering, Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfilment of the requirement for the degree of Master of Science (MSc) in Engineering